Gender differences in motivation and learning style preferences among pre-sessional students in IIUM - Nur Hafezah Hussein (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
Understanding the differences among ESL learners is very crucial since it helps as a means to improving the ESL learning. It has also been noted that there are many factors that influence second language learning such as age, gender, motivation, anxiety, learning styles and strategies, as well as culture. Among these, gender is considered to have a significant impact on students' second language learning. This study sought to investigate gender differences in the motivation and learning style preferences in learning English as a second language among 100 female and male presessional students enrolled in the International Islamic University Malaysia. The study employed a survey design which involved administering of a questionnaire that consists of an adapted version of Gardner's (1985) Attitude/Motivation Test Battery (AMTB), and Reid's Perceptual Learning Style Preference Questionnaire (1987). The findings of the study show that there were no statistically significant differences existing in the motivation to learn English between male and female pre-sessional students in IIUM. However, it is found that gender effect was significant between male and female students in their preferred learning styles where the female reported stronger preference in auditory and tactile learning styles. Finally, implications of the findings are discussed.